(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2013)
يتناول هذا البحث موضوعاً اقتصادياً هاماً حظي باهتمام كبير من قبل الحكومة وقطاع الأعمال في سورية وهو موضوع الشراكة بين القطاعين العام والخاص في إدارة المرافق الاقتصادية، ويناقش هذا البحث تجربة التشاركية في قطاع النقل البحري وبالتحديد في مرفأ اللاذقية. سيتناول البحث واقع مرفأ اللاذقية ودوره في التجارة الخارجية السورية والأسباب التي دعت إلى تطبيق التشاركية في إدارة نشاط الحاويات والأهداف التي حددتها شركة المرفأ وواقع العمل في محطة حاويات اللاذقية. ويهدف البحث إلى تقويم تجربة التشاركية في مرفأ اللاذقية من خلال تحليل واقع عمل شركة محطة حاويات اللاذقية الدولية والنتائج التي حققتها خلال السنوات الثلاث الأولى والفوائد التي حققتها شركة مرفأ اللاذقية من تطبيق التشاركية، وسيصل البحث إلى نتائج مهمة وبعض التوصيات لتطوير تجربة التشاركية في مرفأ اللاذقية بشكل خاص وقطاع النقل البحري بشكل عام. This research addresses an important economic issue, which is the subject of partnership between the public and private sectors in economic facilities management, this research discusses the participatory experience in the maritime transport sector, specifically in Lattakia port. The research will address the reality of Lattakia port situation and its role in the Syrian foreign trade and the reasons for the application of participatory management of containers activity and targets set by the port company, and the nature of working in Lattakia container terminal. The research aims to assess the experience of participatory in Lattakia port, through the analysis the nature of Lattakia international container terminal(LICT (company, and results achieved during the first three years, and the benefits that Lattakia port company achieved by the application of participatory, and will search to the important results and some recommendations for the development experience of participatory in Lattakia port particular, and the maritime transport sector in general.